Peritonectomy HIPEC—contemporary results, indications - Morris, David L. (Chinese Journal of Cancer Research; Vol 25, No 4 (August 24, 2013): Chinese Journal of Cancer Research, 2013)
Paul Sugarbaker’s procedural description in this paper (1) comes from the pioneer and master of this area. His original description of peritoneal cancer index (PCI) and cytoreduction score (CC) is also fundamental to selection of patients and intraoperative assessment. PCI is calculated by dividing the abdomen into 9 areas and 4 additional scores for the small bowel (Figure 1).